Applications and Perspectives of Cascade Reactions in Bacterial Infection Control - Li, Yuanfeng; Yang, Guang; Ren, Yijin; Shi, Linqi; Ma, Rujiang; van der Mei, Henny C.; Busscher, Henk J. (Frontiers in Chemistry, 2020)
Cascade reactions integrate two or more reactions, of which each subsequent reaction can only start when the previous reaction step is completed. Employing natural substrates in the human body such as glucose and oxygen, cascade reactions can generate reactive oxygen species (ROS) to kill tumor cells, but cascade reactions may also have potential as a direly needed, novel bacterial infection-control strategy. ROS can disintegrate the EPS matrix of infectious biofilm, disrupt bacterial cell membranes and damage intra-cellular DNA. Application of cascade reactions producing ROS as a new infection-control strategy is still in its infancy. Main advantages for infection-control cascade reactions include the fact that they are non-antibiotic based and induction of ROS resistance unlikely. However, the amount of ROS generated is generally low and antimicrobial efficacies reported are still far less than 3 to 4 log units necessary for clinical efficacy. Increasing the amounts of ROS generated by adding more substrate, bears the risk of collateral damage to tissue surrounding an infection site. Collateral tissue damage upon increasing substrate concentrations may be prevented by locally increasing substrate concentrations, for instance using smart nanocarriers. Smart, pH responsive nanocarriers can self-target and accumulate in infectious biofilms from the blood circulation to confine ROS production inside the biofilm to yield long-term presence of ROS, despite the short-life time (nanoseconds) of individual ROS molecules. Increasing bacterial killing efficacies using cascade reaction components containing nanocarriers constitutes a first, major challenge in the development of infection-control cascade reactions. Nevertheless, their use in combination with clinical antibiotic treatment may already yield synergistic effects, but this remains to be established for cascade reactions. Furthermore, specific patient groups possessing elevated levels of endogenous substrate (for instance diabetic or cancer patients) may benefit from the use of cascade reaction components containing nanocarriers.